The effect of the Take Charge intervention on mood, motivation, activation and risk factor management: Analysis of secondary data from the Taking Charge after Stroke (TaCAS) trial. (July 2021) - McNaughton, Harry; Weatherall, Mark; McPherson, Kathryn; Fu, Vivian; Taylor, William J; McRae, Anna; Thomson, Tom; Gommans, John; Green, Geoff; Harwood, Matire; Ranta, Annemarei; Hanger, Carl; et al.
Objective: To use secondary data from the Taking Charge after Stroke study to explore mechanisms for the positive effect of the Take Charge intervention on physical health, advanced activities of daily living and independence for people after acute stroke. Design: An open, parallel-group, randomised trial with two active and one control intervention and blinded outcome assessment. Setting: Community. Participants: Adults ( n  = 400) discharged to community, non-institutional living following acute stroke. Interventions: One, two, or zero sessions of the Take Charge intervention, a self-directed rehabilitation intervention which helps a person with stroke take charge of their own recovery. Measures: Twelve months after stroke: Mood (Patient Health Questionnaire-2, Mental Component Summary of the Short Form 36); 'ability to Take Charge' using a novel measure, the Autonomy-Mastery-Purpose-Connectedness (AMP-C) score; activation (Patient Activation Measure); body mass index (BMI), blood pressure (BP) and medication adherence (Medication Adherence Questionnaire). Results: Follow-up was near-complete (388/390 (99.5%)) of survivors at 12 months. Mean age (SD) was 72.0 (12.5) years. There were no significant differences in mood, activation, 'ability to Take Charge', medication adherence, BMI or BP by randomised group at 12 months. There was a significant positive association between baseline AMP-C scores and 12-month outcome for control participants (1.73 (95%CI 0.90 to 2.56)) but not for the Take Charge groups combined (0.34 (95%CI −0.17 to 0.85)). Conclusion: The mechanism by which Take Charge is effective remains uncertain. However, our findings support a hypothesis that baseline variability in motivation, mastery and connectedness may be modified by the Take Charge intervention.